Structure of the nuclear stellar cluster of the Milky Way galaxy. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Kunneriath, Devaky; Schödel, Rainer; Stolovy, Susan; Feldmeier, Anja
Abstract: Nuclear star clusters are unambiguously detected in about 50–70% of spiral and spheroidal galaxies. They have typical half-light radii of 2–5 pc, dynamical mass ranging from 10 6 – 10 7 M⊙, are brighter than globular clusters, and obey similar scaling relations with host galaxies as supermassive black holes. The nuclear stellar cluster (NSC) which surrounds Sgr A*, the SMBH at the center of our galaxy, is the nearest nuclear cluster to us, and can be resolved to scales of milliparsecs. The strong and highly variable extinction towards the Galactic center makes it very hard to infer the intrinsic properties of the NSC (structure and size). We attempt a new way to infer its properties by using Spitzer MIR images in a wavelength range 3–8 μm where the extinction is at a minimum, and the NSC clearly stands out as a separate structure. We present results from our analysis, including extinction-corrected images and surface brightness profiles of the central few hundred parsecs of the Milky Way.